Detection and maintenance for railway track defects: A review - Li, Jie; Doh, Shu Ing; Manogaran, Rachel (IOP Science, 2023)
Steel rail has been at the heart of rail transportation systems for nearly a hundred years. With the rapid development of railway transportation, the steel rail operates in high-speed and heavy-duty operating environment. Steel rail is prone to damages; thus, frequency inspection and maintenance is required to prolong the lifespan of it. Failing to proper periodical inspection and maintenance shall result to accidents which cause injuries and fatality, high repair cost and loss of public confidence. Despite advances in inspection and maintenance technology in railway engineering, the ever-increasing demand for services has resulted in railway failures continuing to be a significant economic burden and jeopardizing the safe operation of railways. This paper reviewed the common defects of rails, the steel rail treatment methods and the application of new inspection equipment.